2018
DOI: 10.1038/s41467-018-06633-z
|View full text |Cite
|
Sign up to set email alerts
|

Interface-mediated hygroelectric generator with an output voltage approaching 1.5 volts

Abstract: Hygroelectricity is proposed as a means to produce electric power from air by absorbing gaseous or vaporous water molecules, which are ubiquitous in the atmosphere. Here, using a synergy between a hygroscopic bulk graphene oxide with a heterogeneous structure and interface mediation between electrodes/materials with Schottky junctions, we develop a high-performance hygroelectric generator unit with an output voltage approaching 1.5 V. High voltage (e.g., 18 V with 15 units) can be easily reached by simply scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
255
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(262 citation statements)
references
References 43 publications
1
255
1
5
Order By: Relevance
“…e,f) Reproduced under the terms of the CC-BY Creative Commons Attribution 4.0 International license (https://creativecommons.org/licenses/by/4.0). [37] Copyright 2018, The Authors, published by Springer Nature. stacks of graphene sheets gives an output power density of up to ≈0.42 µW cm −2 .…”
Section: Specific Surface Areamentioning
confidence: 99%
“…e,f) Reproduced under the terms of the CC-BY Creative Commons Attribution 4.0 International license (https://creativecommons.org/licenses/by/4.0). [37] Copyright 2018, The Authors, published by Springer Nature. stacks of graphene sheets gives an output power density of up to ≈0.42 µW cm −2 .…”
Section: Specific Surface Areamentioning
confidence: 99%
“…In addition, GO with gradient oxygen‐containing groups, which can also generate electricity by absorbing water molecules, has also been used in humidity sensors . Several methods, including moisture‐electric annealing, gradient laser reduction, and gradient thermal reduction, have been developed for preparing GO with an oxygen‐containing group gradient …”
Section: Skin‐inspired Humidity Sensorsmentioning
confidence: 99%
“…First of all, the strategy of partially directional thermal reduction was proposed for moist electric generator to realize an asymmetric porous graphene oxide (GO) membrane with a considerable open‐circuit voltage approaching 450 mV in ambient condition 24 . Furthermore, Huang et al 25 revealed that gradient‐reduced GO together with a thick GO layer utilized as hygroscopic materials in the moist electric generator could supply a high voltage of 1.5 V. The heterogeneous configuration that can regulate ion migration contributed to excellent performance in this device. Then, laser processing was chosen to assemble a series of shape‐deformable miniaturized graphene‐based moist electric generator with potential applications in special and strict working conditions (Figure 14).…”
Section: The Versatile Applications Of 2d Group‐iva Materialsmentioning
confidence: 99%